2014
DOI: 10.1155/2014/539540
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Vitamin Eδ-Tocotrienol in Collagen-Induced Rat Model of Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory disease primarily involving inflammation of the joints. Although the management of the disease has advanced significantly in the past three decades, there is still no cure for RA. The aim of this study was to determine the therapeutic efficacy of δ-tocotrienol, in the rat model of collagen-induced arthritis (CIA). Arthritis was induced by intradermal injection of collagen type II emulsified in complete Freund's adjuvant. CIA rats were orally treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
1
22
0
3
Order By: Relevance
“…Using female rats with collagen-induced arthritis (CIA), Radhakrishnan et al (2014) revealed that the animals orally treated with γT3 (5 mg/kg) for 25 days (day 21 to day 45) had lower hind paw thickness and edema compared to untreated arthritic animals [169]. Similar outcomes were obtained from another study by Haleagrahara et al (2014), whereby oral supplementation of δT3 (10 mg/kg) exerted significant impact in lowering both left and right hind paw edema in the CIA animals [170]. The researchers also investigated the involvement of inflammatory response and oxidative stress in this CIA model.…”
Section: Effects Of Tocotrienol On Arthritissupporting
confidence: 58%
See 1 more Smart Citation
“…Using female rats with collagen-induced arthritis (CIA), Radhakrishnan et al (2014) revealed that the animals orally treated with γT3 (5 mg/kg) for 25 days (day 21 to day 45) had lower hind paw thickness and edema compared to untreated arthritic animals [169]. Similar outcomes were obtained from another study by Haleagrahara et al (2014), whereby oral supplementation of δT3 (10 mg/kg) exerted significant impact in lowering both left and right hind paw edema in the CIA animals [170]. The researchers also investigated the involvement of inflammatory response and oxidative stress in this CIA model.…”
Section: Effects Of Tocotrienol On Arthritissupporting
confidence: 58%
“…The researchers also investigated the involvement of inflammatory response and oxidative stress in this CIA model. Both γT3 and δT3 were capable of decreasing inflammation (reduced CRP and TNF-α) and oxidative stress (increased SOD and total glutathione (GSH)) in the CIA rats [169,170]. A recent study showed that annatto tocotrienol at 100 mg/kg prevented cartilage degeneration in a rat model of osteoarthritis induced by monosodium iodoacetate, as evidenced by reduced histological scoring and circulating cartilage oligomeric matrix protein level in the treated rats [171].…”
Section: Effects Of Tocotrienol On Arthritismentioning
confidence: 99%
“…Vitamin E delta-tocotrienol (VEDT), a natural vitamin E compound, is receiving increasing attention as a potential chemopreventive and/or chemotherapeutic agent [ 14 , 18 , 19 ]. Several studies in vitro and in vivo have demonstrated antitumor activity of VEDT [ 10 , 16 , 17 , 20 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to prescription pharmaceutical and biological interventions, several natural products have been evaluated in collagen-induced arthritic rats. Most recently, the beneficial effects of d-tocotrienol (10 mg/kg) on reducing paw edema and improving histopathological features when administered on days 25 through 50 post-collagen injection were reported [51]. Similarly, oral administration of the probiotic Lactobacillus casei improved the individual histopathology scores and overall arthritis score, along with reducing the levels of several inflammatory cytokines [52].…”
Section: Discussionmentioning
confidence: 98%